Three-dimensional printing of a β-tricalcium phosphate scaffold with dual bioactivities for bone repair. Issue 4 (15th February 2021) - Duan, Mengna; Ma, Sijia; Song, Chunyan; Li, Jie; Qian, Ming
Abstract: β-Tricalcium phosphate (β-TCP) had been widely used in the field of bone defect repair because of its osteoconduction and osteoinduction properties. However, for critical-sized bone defects, β-TCP scaffolds need to be functionalised to enhance osteoinduction and antibacterial activity. In this study, we proposed a protocol for mimicking a mussel adhesion mechanism to immobilise bone morphoprotein 2 mimetic peptide (BMP2-MP) and Ornithodoros savignyi (OS) on a three-dimensionally printed β-TCP scaffold. BMP2-MP and the OS polypeptides containing the YKYKY tail were converted into 3, 4‐dihydroxyphenylalanine (DOPA) molecules via hydroxylase. The surface morphology and phase composition of the different scaffolds were analysed via scanning electron microscopy and X-ray diffraction. In addition, the binding activity of BMP2-MP and OS containing the DOPA tail to the scaffold were evaluated. The antibacterial activity of the different scaffolds was studied in vitro by performing bacteriostatic experiments against Escherichia coli and Staphylococcus aureus . The osteoinduction capability of the different scaffolds was evaluated by detecting osteogenesis-associated genes via quantitative polymerase chain reaction and by determining alkaline phosphatase expression levels. Our results demonstrated that introduction of the DOPA tail enhanced the binding capability of BMP2-MP and OS with the β-TCP scaffold, thereby enhancing the antibacterial and osteoinduction capabilities of the scaffold. A scaffold with strong antibacterial and osteoinduction capability will have good application prospects in the field of critical-sized bone defect repair.